2009
DOI: 10.12968/bjom.2009.17.3.40076
|View full text |Cite
|
Sign up to set email alerts
|

Birth centres in the East Midlands: views and experiences of midwives

Abstract: In order to investigate midwives' views and experiences of working at birth centres a qualitative interview study was performed at three birth centres in the UK. Nine midwives were recruited for personal interviews via snowball sampling. Qualitative content analysis was undertaken with the identification of categories and themes. Autonomy of practice emerged as the main category with five subcategories: midwifery aspects, professional development, flexibility and work demand, independence and interprofessional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(24 citation statements)
references
References 10 publications
2
22
0
Order By: Relevance
“…This result has also been described by others (18) and can be understood based on the different contexts of AMU/FMU and obstetric units; the latter is the main work setting for most midwives in Norway. Obstetric-led units are heavily medically influenced by both doctors and midwives (10).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…This result has also been described by others (18) and can be understood based on the different contexts of AMU/FMU and obstetric units; the latter is the main work setting for most midwives in Norway. Obstetric-led units are heavily medically influenced by both doctors and midwives (10).…”
Section: Discussionsupporting
confidence: 81%
“…These settings require midwives to be trained in the skills of normal birth (12)(13)(14). Care in midwifery units is associated with promoting the midwife-mother relationship, facilitating a sense of higher satisfaction and autonomy for both mothers and midwives (13,(15)(16)(17)(18)(19). An American study noted that midwives' experiences of the birth centre atmosphere are described as relaxing, quiet, and less restricted with respect to time and guidelines (20).…”
Section: Introductionmentioning
confidence: 99%
“…Although Thorgen and Crang-Svalenius' (2009) study had a relatively smaller sample size, there was heterogeneity, and the findings were congruent with other studies. All participants in the studies had several years of clinical experience and were females, except for 1 study that also interviewed a male midwife (Carolan-Olah et al, 2015).…”
Section: Negative Perceptions Of Physiological Birthsupporting
confidence: 82%
“…Marquis and Huston () explained that the more involved an individual is with his/her work, the higher their job satisfaction. Thorgen and Crang‐Svalenius () examined midwives' views and experiences of working in birth centres and found that despite the demanding workload, the midwives experienced a sense of accomplishment and fulfilment when they were able to exercise autonomy and utilize their midwifery skills. Similarly, midwives strongly felt that they play pivotal roles in determining a fulfilling birth experience for their patients.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation